Pengaruh Beban Kerja Mental Terhadap Waktu Respon Pengemudi di Kondisi Lalu Lintas Pedesaan dan Perkotaan - Lita Setiawati; Lahay, Idham Halid; Wolok, Eduart; Nugroho, Sinung; Nugroho, Hastiya Annisa Fitri; Nugroho, Mutiara Kurnia (Jurnal Teknik, 2025)
Mental workload is one of the factors that affect driver safety. This study examines the effect of mental workload on truck driver response time in rural and urban traffic conditions. Mental workload was measured using the NASA-TLX questionnaire and physiological measurements using HRV and EEG. Response time was tested using detection simulation. The results showed that drivers experienced moderately high mental workload, with the urban environment showing cognitive enhancement based on alpha signals and LF variables. However, regression analysis found no significant relationship between mental workload and driver response time in either rural or urban environments. This study provides insight that while traffic conditions may affect the level of mental workload of drivers, the impact on response time is not always significant. These findings can serve as a basis for further research in understanding the relationship between mental workload, traffic conditions and driving safety.